The interplay of cholinergic function, attention, and falls in Parkinson's disease - Yarnall, Alison; Rochester, Lynn; Burn, David J. (Movement disorders, 2011)
Dopamine loss in the substantia nigra causes several of the motor signs seen in Parkinson's disease, but there is now increasing evidence highlighting the importance of cholinergic loss in the pathophysiology of nonmotor symptoms. The nucleus basalis of Meynert supplies the majority of the cholinergic input to the cerebral cortex, with the pedunculopontine nucleus providing many subcortical structures with acetylcholine. Both these structures undergo degeneration in Parkinson's disease (PD), with more severe loss associated with cognitive impairment. The risk of dementia in PD is greater than that in control subjects, with impairments in attention, visuospatial function, and executive control dominating. Imaging studies have demonstrated degeneration of the cholinergic system in PD, Parkinson's disease dementia, and dementia with Lewy bodies, with improvements in attention seen following the introduction of cholinesterase inhibitors. Conversely, anticholinergic drugs are associated with cognitive decline, with neuropathology studies indicating the presence of increased neurofibrillary tangles and senile plaque formation. In addition, these drugs are also known to precipitate visual hallucinations, lending support to a cholinergic basis for visual hallucinations in PD. Gait, falls, and cognition may also be related, as evidenced by the findings that fallers perform less well on test of attention than nonfallers and that greater postural instability is associated with worse scores on attention and executive function. It is therefore feasible that cognition (namely, attention), visual hallucinations, falls, and gait are subserved by acetylcholine, and this is further explored in this clinically orientated review. © 2011 Movement Disorder Society